Complex dynamics and the development of behavioural individuality. (April 2018) - Fisher, David N.; Brachmann, Matthew; Burant, Joseph B.
Highlights: Behavioural differences may arise in the absence of genetic or environmental variation. Chaotic dynamics may influence behavioural development and among-individual variation. We discuss methods and experimental designs to test this idea. Nonlinear and chaotic behavioural development may explain much of natural variation.